Mobility and adsorption of liquid organic hydrogen carriers (LOHCs) in soils – environmental hazard perspective. Issue 19 (23rd September 2020) - Zhang, Ya-Qi; Stolte, Stefan; Alptekin, Gizem; Rother, Alica; Diedenhofen, Michael; Filser, Juliane; Markiewicz, Marta
Abstract : Investigation of the mobility of liquid organic hydrogen carriers in soils in relation to the environmental hazard assessment. Abstract : Liquid organic hydrogen carriers (LOHCs) are an energy system that can be used to store and transport hydrogen under standard temperature and pressure chemically bound to a carrier. The LOHC systems show advantages over conventional energy systems (recyclability, higher sustainability and lower emissions) and other hydrogen-based systems (lower loses, ease of handling and higher safety), and are applied in stationary and mobile applications worldwide. The scale and type of use indicate that the release of LOHCs to the environment can be expected. Yet, their behaviour and fate have not been investigated especially with regard to assessment of exposure, mobility and possibility to reach surface water, groundwater or drinking water sources. To investigate that we studied the mobility of thirteen technologically promising LOHC candidates including indole, quinaldine, carbazole derivatives, benzyltoluene and dibenzyltoluene, and their (partially) saturated forms in soil, for the first time. The substances were classified into mobility classes based on their organic carbon–water partition coefficients ( K oc ) determined via in silico models and HPLC screening. The log  K oc values increased in the order indoles < quinaldines < carbazole derivatives < benzyltoluenes < dibenzyltoluenes covering a full spectrum of mobility scale (from highly mobile to immobile). The behaviour of exemplary LOHC system – quinaldine including H2 -unsaturated, partially and fully saturated forms – was further assessed by investigating the soil-water partition coefficients ( K d ) via adsorption batch equilibrium and column leaching test. The study showed that some LOHCs can be expected to be very mobile in soils and have the potential to reach groundwater.